2013
DOI: 10.1002/clen.201200093
|View full text |Cite|
|
Sign up to set email alerts
|

Adsorption of Complex Pollutants from Aqueous Solutions by Nanocomposite Materials

Abstract: In view of water pollutants becoming more complex, both anionic and cationic pollutants need to be removed. The multi‐pollutants simultaneous removal is paid more and more attention. Hence, development composite materials for treatment complex wastewater are the aim of this study. In this research, iron–nickel nanoparticles deposited onto aluminum oxide (α‐Al2O3) and carbon nanotubes (CNTs) to form nanocomposite materials Fe–Ni/Al2O3 and Fe–Ni/CNTs, respectively, were used as adsorbents. The adsorption capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The result shows that the use of n Fe 3 O 4 and fly ash for the preparation of n Fe 3 O 4 /fly ash composites greatly increase the surface area of the precursors. The increase in the surface area is in support of the work by Wang et al who reported the deposition of iron–nickel nanoparticles onto carbon nanotubes (CNTs) to form nanocomposite materials.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The result shows that the use of n Fe 3 O 4 and fly ash for the preparation of n Fe 3 O 4 /fly ash composites greatly increase the surface area of the precursors. The increase in the surface area is in support of the work by Wang et al who reported the deposition of iron–nickel nanoparticles onto carbon nanotubes (CNTs) to form nanocomposite materials.…”
Section: Resultssupporting
confidence: 71%
“…Activated carbon is regarded as an effective material for controlling both organic and inorganic pollutants. Nevertheless, many authors have intensively investigated other materials such as coal and wood fly ash , biosorbents , agricultural wastes , nano particles , and composites for the remediation of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The high adsorption performance of graphene sheets mainly is due to the large surface area and graphitized basal plane structure of it, which could provide excellent conditions for adsorption of dyes. 31 However, in the presence of Ag/CuFe 2 O 4 /rGO nanocomposite, the removal efficiency of MB is increased to 100% indicating the as-prepared nanocomposite is more suitable and superior. The Ag and CuFe 2 O 4 nanoparticles on the surface of graphene prohibit the restacking of its layers and thus increase the surface area and adsorption capacity of the composite.…”
Section: Effect Of the Initial Concentration Of Mbmentioning
confidence: 98%
“…27,28 One of the applications of graphene-based materials is also the removal of organic dye pollutants from water. 29,30 Many polymeric and inorganic adsorbents such as carbon-based materials, 31 porous metal oxides, 32 clays, 33 chitosan, 34 zeolites, 35 and metal-organic frameworks (MOFs) 36 have developed for adsorption removal of pollutants from aqueous solutions. Among them, carbonous materials such as graphene have shown excellent performance in adsorption of organic contaminants from water.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,9 The adsorption processes have proven to be one of the best treatment methods because of their high efficiency, low price, easy operation and handling. 1,4,6,9,10 Different types of natural and synthetic adsorbents have been used to treat wastewaters containing dyes including CNTs, 1,5 agricultural waste, 2,4 graphene oxide, 6 activated carbons, 11 zeolite, 12 clay, 13 polymers 7,14 and their composites. However, disadvantages of these adsorbents are low adsorption capacities and separation inconvenience.…”
Section: Introductionmentioning
confidence: 99%